The rise of Kyoshi - Yee, F. C. (Amulet books, 2019)
F. C. Yee's The Rise of Kyoshi delves into the story of Kyoshi, the Earth Kingdom-born Avatar. The longest-living Avatar in this beloved world's history, Kyoshi established the brave and respected Kyoshi Warriors, but also founded the secretive Dai Li, which led to the corruption, decline, and fall of her own nation. The first of two novels based on Kyoshi, The Rise of Kyoshi maps her journey from a girl of humble origins to the merciless pursuer of justice who is still feared and admired centuries after she became the Avatar.